Imaging in Latest Dentistry - A Review - Sharma, Dr. Yesh; Marwaha, Dr. Jasmine; Bishnoi, Dr. Raju Ram; Goyal, Ruchika; Biswas, Dr. Anwesha (International Journal of Innovative Research in Medical Science, 2019)
Endodontics is the branch of dentistry in which radiology plays a critical indispensable role. Radiology illuminates what otherwise would be dark and hidden zones and allows the dentists to visualize areas not accessible by other diagnostic means. It is the use of oral radiographs which enables visualization of the bone around the apices of the teeth, as well as the results of the root canal treatments, and as such it has allowed turning endodontics into a scientific professional entity.